Pengembangan Molecular Imprinted Polymer Untuk Pemisahan Vitamin C dalam Sediaan Multivitamin - Untung Gunawan; Eko Adi Prasetyanto; Shannen Ivanka Gunardi (Jurnal Farmasi Indonesia, 2021)
Vitamin C has chromophore group that can be analyzed using UV-Vis spectrophotometry, however if the complex matrix to be analyzed like multivitamins, a selective separation method is required to eliminate matrix interferences. One of the selective separation methods is Molecular Imprinted Polymer (MIP) which which hasn’t been widely used in multivitamin samples. The purpose of this study was to obtain selective MIP for separation of vitamin C in multivitamins.. Research methods included interaction observation of vitamin C with functional monomers using UV spectrophotometry, MIP was synthesized using bulk method for 24 hours at 60 °C. MIP was characterized using spectrophotometry, infrared and scanning electron microscopy MIP selectivity were determined by determination of imprinting factor and its recovery with the liquid-liquid extraction method (LLE) and SPE C18 for separation of vitamin C in multivitamin samples on the market using a validated method. Hypsochromic shift showed interaction between vitamin C and functional monomers, which hydrogen bonds were taking role in MIP synthesis. Imprinting factor more than 1 and recovery value close to 100% indicated MIP selectivity to vitamin C. MIP-1 had the highest selectivity compared to the ECC and SPE C18 methods for separation of vitamin C in multivitamin samples with recovery of 98.17 ± 2.31%, 69.42 ± 3.01%, and 93.26±4.24% respectively. Synthesized MIP-1 was selective for the separation of vitamin C in multivitamins.